It's been a decade: The Swiss Young Neurosurgeons Society. Issue 1 (20th June 2018) - Murek, M; Jilch, A; El-Rahal, A; Zubak, I; Fung, C; Abu-Isa, J; Fichtner, J; Actor, B; Khan, N; von Campe, G; Radovanovic, I; Kuhlen, D; et al.
The Swiss Young Neurosurgeons Society (SYNS) comes to life in 2008, creating a community renowned for its unique spirit, a platform dedicated to lifelong teaching and learning. In 2008, a small group of Swiss residents found a cross-canton training platform to provide dedicated, affordable courses organized by residents to directly support their peers. After almost 10 years, SYNS thrives on its unique, familial spirit cultivating a direct contact with teachers as well as with their supporters. The society provides up to four annual training courses and serves as an open platform for residents to exchange experiences and to represent their members' interests on a national and international level.